(untitled) (المجلة الدولية للبحوث العلمية, 2024)
The healthcare sector in Saudi Arabia is undergoing a remarkable transformation driven by factors such as population growth and rising disposable income. This has led to a significant surge in demand for private healthcare services, particularly in major cities like Riyadh. While catering to the needs of a growing patient base, there is an urgent need to ensure patient-centered care to enhance service quality and satisfaction. Multiple research studies have affirmed the positive impact of patient engagement. Studies consistently demonstrate that patients actively involved in their healthcare decisions experience improved quality of life, better adherence to treatment, and reduced hospital readmission rates. This ultimately leads to improved health outcomes and reduced overall healthcare costs. Despite these well-established benefits, many private healthcare institutions in Riyadh struggle to effectively integrate patient engagement strategies into their practices. This implementation gap necessitates a deeper understanding of the factors influencing these efforts. This study aims to address this pressing need by investigating the factors affecting patient engagement initiatives within private healthcare institutions in Riyadh. The study will explore the influence of three key domains: Digital Technology: The increasing reliance on digital tools in healthcare holds the potential to revolutionize patient engagement. This study will explore how technology platforms, telemedicine applications, and patient portals can facilitate patient engagement. Organizational Leadership: Leadership plays a pivotal role in fostering a patient-centered care culture. This research will examine how leadership styles, commitment to patient engagement, and resource allocation impact patient engagement initiatives. Organizational Culture: The overall culture of a healthcare institution significantly influences patient interactions. This study will explore how factors such as communication practices, staff training, and patient empowerment within the organizational culture shape patient engagement. By examining these three domains, the study aims to provide valuable insights into the factors that influence patient engagement in private healthcare settings in Riyadh. The findings will contribute to the development of effective strategies for enhancing patient engagement and improving overall healthcare quality.